Type 2 diabetes and chronic kidney disease combinations in heart failure across the ejection fraction spectrum: clinical associations, medication use, and cause-specific outcomes: a contemporary, real-world analysis of the Swedish Heart Failure Registry - Giulia Ferrannini; Tymon Pol; Charlotta Ljungman; Ulf Dahlström; Aurora Merolla; Lars H Lund (European Journal of Heart Failure, 2026)
Abstract Aims The interactions between heart failure (HF), chronic kidney disease (CKD), type 2 diabetes mellitus (T2DM), and relative drug use remain poorly studied. Methods Patients enrolled in the Swedish HF registry 2017–2023 were divided according to CKD and T2DM. HF medication use and all-cause death, cardiovascular death, first HF hospitalization (HHF), their composite, and end-stage renal disease (ESRD) were assessed. Results Among 54 341 patients (34% females, mean age 73 years), 51% had no CKD/no T2DM, 24% CKD only, 14% T2DM only, and 11% both CKD/T2DM. CKD only and CKD/T2DM prevalences were higher in HF with preserved ejection fraction (HFpEF; 29% and 15%, respectively) than with mildly reduced EF (HFmrEF; 23% and 11%) and reduced EF (HFrEF 22% and 10%). HF medication use, especially of mineralocorticoid receptor antagonists, was generally lower in groups with CKD. Event rates for all outcomes were progressively higher going from no CKD/no T2DM, T2DM only, CKD only, and both CKD/T2DM in all EF categories. Independent risks of mortality and HF outcomes were significantly increased in the presence of CKD/T2DM, whereas for ESRD, T2DM alone did not significantly increase risk, CKD alone increased it threefold, and both CKD and T2DM increased it six-fold. CKD added more to the risk of events in HFrEF than in HFpEF. Conclusion CKD was more common in HFpEF and a strong independent risk factor for all outcomes. T2DM was a moderate independent risk factor for all outcomes. These findings inform drug implementation and future aldosterone-targeting drug trials.